Remote Delivery of Psychosocial Intervention for College Students with ADHD during COVID-19: Clinical Strategies, Practice Recommendations, and Future Considerations. Issue 1 (2nd January 2021) - Oddo, Lauren E.; Garner, Anna; Novick, Danielle R.; Meinzer, Michael C.; Chronis-Tuscano, Andrea
ABSTRACT: The COVID-19 pandemic is an unprecedented social-emotional stressor significantly impacting intervention services for at-risk college students with attention-deficit/hyperactivity disorder (ADHD). In order to succeed in the new remote learning context, students are tasked with employing strong organizational, time management, and planning skills. They must self-regulate thoughts, actions, and emotions, inhibit task-irrelevant activity, and cope with unprecedented stressors. These ingredients for success nearly completely overlap with the core dysfunctions of ADHD. Recognizing the importance of providing psychosocial services during this high-risk time and in response to social distancing and university guidelines, we initiated a telehealth version of our program for college students with ADHD (i.e., SUCCEEDS). In the current paper, we describe novel and creative clinical strategies designed to assist students with ADHD in problem solving, adaptive coping, organizational skills, and time management strategies during the COVID-19 pandemic. Specifically, we: (1) detail the initial set-up of remote delivery services and supervision, (2) describe key components of the SUCCEEDS program developed to support students' unique needs during the COVID-19 pandemic, (3) present focus group and qualitative feedback from SUCCEEDS coaches and students, (4) provide an illustrative case vignette of application, and (5) discuss future directions and "lessons learned" in moving SUCCEEDS to a remote platform. In so doing, our hope is to contribute to an ongoing dialog surrounding optimal delivery of remote services to college students with ADHD, particularly during high-risk periods.